The Gift of Administration : New Testament Foundations for the Vocation of Administrative Service - Senior, Donald (Book collections on Project MUSE., 2016)
In his First Letter to the Corinthians Paul cites "administrators" as one of God's gifts to the Christian community (1 Cor 12:28). But many who serve in administrative service today have difficulty seeing how their everyday work is an expression of discipleship. This book, written by an experienced administrator and noted biblical scholar, shows how the various functions of institutional administration are deeply rooted in the Scriptures and are a genuine expression of our call to discipleship. Leadership, mission statements and planning, finances and fund raising, personnel issues, communications, and public relations -- all of these seemingly "secular" activities serve to build up the Body of Christ and deserve to be recognized as authentic Christian ministry. To see administrative service as a biblically rooted gift can help those involved in this way of life to find deeper and more satisfying spiritual meaning in what they do.